PLANO SISTEMATIZADO DE INTERVENÇÕES DE ENFERMAGEM PARA UNIDADES INTENSIVAS PEDIÁTRICAS À LUZ DA TEORIA DAS NECESSIDADES HUMANAS BÁSICAS - Lopes, Guilherme dos Santos (2017)
Introduction: The systematization of nursing assistance (SAE), from specific knowledge and critical reflection on the organization, management and philosophy of nursing, constitutes an instrument of fundamental importance to the management, optimization and qualification of nursing care. Although nurses have already science and the perceived need of the implementation of SAE, as recommended by Resolution COFEN 358/2009, the methodological process and the choice of an appropriate theoretical framework also constitutes challenge for most professionals. Based on this rationale, this study had as Objectives: general: Create and validate a plan systematized nursing interventions to pediatric intensive care units; specific: Knowing the perception of nurses on the systematization of nursing care in pediatric intensive care units, and describe the stages of construction and validation of a plan of nursing interventions to pediatric intensive care units, in view of the Theory of Basic Human Needs Wanda Aguiar Horta. Methodology: To answer the first specific objective was held one exploratory and descriptive, qualitative, between March and July 2017, with 15 nurses working in a pediatric intensive care unit of a medium-sized hospital in the eastern region of the State of Rio Grande do Sul from individual interviews with guiding questions. The second specific objective was met from the methodological research, descriptive, conducted with ten experts in the field, between the months of July and September 2017, in which we used the Psychometric Theory as the validation process measurement technique. The object concordance rate was at least 80% for validation of the material. Results: From the research data organized and coded by content analysis resulted in two thematic areas, namely: SAE: legal and private process Nurse and SAE: from conception to care practice. Methodological research has yielded a return of ten instruments evaluated by experts in the first and second round of the Delphi cycle. In the first round it was suggested pertinent changes in relation to items and nursing interventions. O instrument was considered valid both in content and appearance and can help to support the implementation of the SAE in pediatric intensive care units at local and national level. Final considerations: It follows that the perception of nurses on the systematization of nursing care in pediatric intensive care units does not differ from other units of professional performance. Nurses, in general, have superficial theoretical knowledge on the theoretical and methodological approach of SAE. Their understanding is limited, in part, in compliance with legal requirements and implementation of the stages of diagnosis and nursing interventions. In this sense, the systematic and validated plan interventions will serve to equip the Nurses professionals working in pediatric intensive units and thus contribute to the improvement and consolidation of the nursing process in health services. As resultant product of the research process will be available a systematic plan and validated to support nursing interventions in pediatric intensive care units. It is recognized that the problems of care practice must be part of the academic discussions, as well as scientific theories need to contribute to the gradual transformation of practices. Integrating and strengthening these realities will result in addition best care practices in commitment to the consolidation of nursing science. It should be noted, finally, the need for further studies in the area, to expand clinical interventions and enable new theoretical insights into the relevance of the systematization of nursing care in different areas of nurse's performance.